Low-threshold GaN thin-film random laser through the weak scattering feedback. (4th January 2017) - Zhu, Hai; Chen, Anqi; Wu, Yanyan; Ji, Xu; He, Yiting; Qiu, Zhiren; Tang, Zikang; Yu, Siufung
Abstract: Room temperature random lasing is demonstrated from a GaN epitaxy film with defect pits that result from growth imperfection. The optical coherence feedback is attributed to the formation of closed-loop paths of light through the scattering effect of the defect pits, which can avoid the difficulty of fabricating an artificial cavity. The random lasing action was also investigated through near and far-field patterns that imaged onto the CCD camera. In addition, the angle distribution of the laser beam was illustrated by use of an angle-resolved spectrometer. The lasing threshold, based on the weak scattering diffusive mode of GaN, is about one order of magnitude lower than that strong scattering random laser (RL). Hence, the results in this paper represent a low-cost technique to realize GaN-based laser diodes without the fabrication difficulty of cavity facets that result from the hardness of the sapphire substrate.